PENGARUH PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY BERBASIS PENDEKATAN PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR BIOLOGI - Rini rini; Jekti Prihatin; Puji Astuti (BIOEDUKASI, 2017)
Course Review Horay (CRH) learning model based on Problem-Based Learning (PBL) is a cooperative learning model that provides many questions to encourage active learning and critical thinking ability of students. Cards of CRH contain 9 or 16 or 25 columns to write down the students' answers. If they answer three questions correctly as vertical/horizontal/diagonally they would shout “horay”. The purpose of this research was to determine the effect of CRH learning model based on PBL approach on the students’ critical thinking skill and learning outcome for the eleventh-grade science students of SMA Arjasa Jember. There were used control class and experimental class. The results showed that learning model of CRH based on PBL approach had increased the students’ critical thinking skill (p = 0.000) aswell as significantly increased the students’ learning outcome of cognitive, affective and psychomotor. Keywords: learning outcomes, critical thinking skill, learning model, approach.